2018
DOI: 10.1016/j.jallcom.2017.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Porosity and pore size effect on the properties of sintered Ti35Nb4Sn alloy scaffolds and their suitability for tissue engineering applications

Abstract: Porous scaffolds manufactured via powder metallurgy and sintering were designed for their structure (i.e. pore size and porosity) and mechanical properties (stiffness, strength) to be controlled and tailored to mimic those of human bone. The scaffolds were realised to fulfil three main objectives: (i) to obtain values of stiffness and strength similar to those of trabecular (or spongy) bone, with a view of exploiting these as bone grafts that permit cell regeneration, (ii) to establish a relationship between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 47 publications
3
11
0
Order By: Relevance
“…In the design of bone scaffolds, the common goal in general is to mimic the structure of the trabecular (cancellous or spongy) bone [30] found in the human body. The trabecular bone has a greatly porous structure, accordingly, the design of high porosity scaffolds is the main criterion in bone tissue engineering.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In the design of bone scaffolds, the common goal in general is to mimic the structure of the trabecular (cancellous or spongy) bone [30] found in the human body. The trabecular bone has a greatly porous structure, accordingly, the design of high porosity scaffolds is the main criterion in bone tissue engineering.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Porosity within human tissues has been extensively investigated in bone and other soft tissues (e.g. adipose tissue) from the perspective of tissue engineering [35][36][37][38]. Nonetheless, the placental maternal IVS porous medium has been less well studied.…”
Section: Discussionmentioning
confidence: 99%
“…The ideal pore size required for skin and bone tissue engineering varies. From the earlier studies, it was found that the pore size ranging from 200 to 400 µm was suitable for bone tissue engineering [ 51 ], whereas the pores ranging from 50 to 200 µm were found to be effective in the smooth muscles and soft tissue engineering process [ 52 , 53 , 54 ]. Natural and synthetic polymers-based sponges have been studied for their potential biomedical applications.…”
Section: Different Forms Of Natural and Synthetic Smart Polymeric Biomaterialsmentioning
confidence: 99%